Beneficial effect of simvastatin on human umbilical vein endothelial cells gap junctions induced by TNF-α. Issue 1 (2nd January 2022) - Ling, Xiwen; Peng, Siyuan; Xu, Yaqin; Chu, Fujiang
ABSTRACT: Although simvastatin has been shown to inhibit vascular permeability, which might be amplified via gap junction intercellular communication (GJIC), the underlying mechanism of action remains unclear. In the present study, we investigated the effects and mechanisms of simvastatin on endothelial cells GJIC. Specifically, human umbilical vein endothelial cells (HUVECs) were stimulated with TNF-α (10 ng/mL) alone or in combination with simvastatin (5 µM), and their effects on vascular endothelial cell GJIC tested via the scrape loading/dye transfer (SL/DT) assay. Next, we performed immunofluorescence, real-time PCR and western blot assays to analyze expression of Cx37, Cx40 and Cx43 in HUVECs. Results showed that GJIC activity in HUVECs was markedly elevated in HUVECs treated with TNF-α in combination with simvastatin. In addition, simvastatin treatment significantly upregulated expression of Cx37 and Cx40 but downregulated Cx43 mRNAs and proteins. Taken together, these marked changes indicated that simvastatin exerts its regulatory effects on gap junction function by upregulating Cx37 and Cx40 and downregulating Cx43 expression.